THE INFLUENCE OF NPL AND CAR ON PROFITABILITY IN NGUDI LESTARI WOMEN'S COOPERATIVE MAGETAN DISTRICT - Anita Fristya; Syamsul Arifin; Lailatul Rohmah (CV Pena Jaya Pers, 2024)
This research aims to determine the effect of NPL (bad credit) and CAR (capital) on profitability at the Ngudi Lestari Women's Cooperative in 2020. Bad credit is calculated using the NPL (Non Performing Loan) ratio, then capital is calculated using the CAR (Capital Adequacy Ratio) ratio. ) and profitability is calculated using the ratio ROA (Return On Assets), ROE (Return On Equity) and NPM (Net Profit Margin). This type of research is quantitative research, using secondary data sources in the form of 2020 financial reports in the form of capital reports, Business Results Calculation Reports, remaining accounts receivable reports, Balance Sheet Reports and Balance Sheet reports. The collection technique is by analyzing archival evidence of the financial reports of the Ngudi Lestari Women's Cooperative in 2020. Data was analyzed using the SPSS version 16 program with descriptive analysis techniques, multiple linear regression analysis, classic assumption tests in the form of normality tests, multicollinearity tests, heteroscedasticity tests and then hypothesis testing. in the form of t test, F test and coefficient of determination test. The results of this research show that bad credit has an insignificant negative effect and capital has a significant positive effect